Pengaruh Latihan Konvensional Dan Akuatik Pada Pemulihan Kemampuan Motorik Penyandang Hemiparesis Pasca Stroke Infark - Bambang Trisnowiyanto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Conventional, Aquatic, Motoric Skill, Hemiparetic, Infarction Stroke. Research objective is to knows how the effects of aquatic training with conventional training to increase motoric skill of hemiparetic patients suffered from infarction stroke. They have got intensive care in Dr. Muwardi Hospital of Surakarta in 2012. These quasi experiment research by design; two group pretest-posttest design, with purposive sampling. Treatment; twice perweek for 6-week intervention. Subjects are 15 men, 5 women with hemiparetic post infarction stroke that have no complicated diseases (41–65 years old). Analyzed based on aquatic group (n=9) and conventional group (n=11) ordering by age match subject ordinal pairing assigned. Results of the anlysis both of aquatic and conventional training have got influnce to increase motoric skill of hemiparetic patients that caused by infarction stroke P=0,000 (α=0,05). The aquatic training has got influnce more than and conventional to increase motoric skill of hemiparetic patients that caused by infarction stroke. Thus these findings indicate that aquatic exercise benefits people with hemiparesis and can be used as a method of exercise rehabilitation for these people.